2006
DOI: 10.1007/s00330-005-0140-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of liver metastases: 16--slice multidetector computed tomography versus superparamagnetic iron oxide-enhanced magnetic resonance imaging

Abstract: The aim of our study was to compare the diagnostic performance of 16--slice multidetector computed tomography with that of superparamagnetic iron oxide (SPIO)-enhanced magnetic resonance (MR) imaging in the detection of small hepatic metastases and in the differentiation of hepatic metastases from cysts. Twenty-three patients with 55 liver metastases and 14 liver cysts underwent SPIO-enhanced MR imaging and multiphasic CT using 16-MDCT. Two observers independently analyzed each image, in random order. Sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
8

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 35 publications
2
33
0
8
Order By: Relevance
“…Rapid sequential imaging with gadolinium-based contrast agents in the extracellular space is superior to unenhanced imaging and helical CT for detecting metastatic liver disease (13). With the recent availability of hepatobiliary contrast medium with uptake into hepatocytes, the detectability and characterization of liver lesions and especially small liver metastases have further improved (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Rapid sequential imaging with gadolinium-based contrast agents in the extracellular space is superior to unenhanced imaging and helical CT for detecting metastatic liver disease (13). With the recent availability of hepatobiliary contrast medium with uptake into hepatocytes, the detectability and characterization of liver lesions and especially small liver metastases have further improved (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Two im- . Three-dimensional GRE MRI using a hepatobiliary contrast agent provides thin sections with no gaps, high signal-to-noise ratio, and high sensitivity for detecting sub-centimeter-sized hepatocellular lesions (5,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies compared MDCT and MRI regarding liver evaluation. It was demonstrated that MRI, either gadolinium-enhanced or with liverspecific SPIO contrast agents, demonstrates a higher diagnostic accuracy than MDCT for detection and characterization of focal liver lesions (30) (Figs. 10, 11).…”
Section: Which Is the Best Modality?mentioning
confidence: 99%